Factors Affection Entrepreneurship Development in Surkhet District - Poudel, Youbaraj (The Gaze: Journal of Tourism and Hospitality, 2024)
Entrepreneurship, an ancient and transformative phenomenon, is pivotal for societal and economic development. It involves identifying innovative ideas and establishing new enterprises, distinguishing itself from self-employment, which lacks entrepreneurial risk-taking, resource mobilization, and production organization. Entrepreneurs significantly contribute to national income and rural prosperity through their ventures. This study employs a mixed-method approach, integrating correlational and causal-comparative research designs to explore factors influencing entrepreneurship development in Surkhet district, Nepal. Data were collected via structured questionnaires with a five-point Likert scale using purposive sampling. Quantitative data were analyzed using SPSS, employing descriptive statistics, correlation and regression analyses, factor analysis, Cronbach’s alpha, and multicollinearity tests. The findings confirm significant relationships between entrepreneurship development and variables such as training, government policies, environmental factors, NGO support, and raw materials availability. These results emphasize the importance of multifaceted support systems for fostering entrepreneurship. Future research is encouraged to explore dynamic policy analysis, policy interactions, and the evolving ecosystem of entrepreneurial development.